Changes, Challenges, and Variations in Neonatal-Perinatal Medicine Fellowship: A View from the Program Directors - Gray, Megan M.; Bruno, Christie; French, Heather; Myers, Patrick; Carbajal, Melissa M.; Reber, Kristina M.; Christou, Helen; Karpen, Heidi; Johnston, Lindsay C.; on behalf of the Organization of Neonatal-Perinatal Medicine Training Program Directors (American Journal of Perinatology, 2022)
Objectives Neonatal-perinatal medicine (NPM) fellowship programs in the United States support >800 learners annually. Understanding variations in the programmatic structure, challenges, and needs is essential to optimize the educational environment and ensure the specialty's future.Study Design NPM fellowship program directors (PDs) and associate program directors (APDs) were invited to complete an electronic survey on their program administration, recruitment, clinical training, assessment methods, scholarly program, and career pathways. Each participant identified individual programmatic strengths, challenges, opportunities, and threats to the field.Results Representatives from 59 NPM fellowships provided data (response rate 59/96 = 61%). In total, 30% of PDs received less than the Accreditation Council for Graduate Medical Education -recommended protected time for administrative duties, and 44% of APDs received no protected time. Fellow clinical service assignments varied widely from 13 to 18 months and 90 to 175 call nights over 3 years. Recruitment practices varied across programs; 59% of respondents raised concerns over the pipeline of applicants. Conflicts between fellows and advanced practice providers were identified by 61% of responders. Programs varied in their scholarly offerings, with 44% of NPM fellowships interested in adding broader research opportunities.Conclusion NPM fellowship leaders identified a need for improved programmatic support, enhanced measures to assess competency, opportunities to strengthen scholarly programs, shared curricular resources, and strategies to balance education with clinical demands. PDs and APDs identified threats to the future of NPM training programs including the diminishing pipeline of applicants into neonatology, challenges with clinical exposure and competence, inadequate support for the educational mission, issues supporting high-quality scholarship, and fewer graduates pursuing physician-investigator pathways. National organizations and academic institutions should take action to address these challenges so that fellowships can optimally prepare graduates to meet their patients' needs.Key Points
Keywords: neonatal-perinatal medicine; fellowship; program director; medical education